PARTISIPASI MASYARAKAT DALAM PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA DIKELURAHAN TEBING TINGGI OKURA KOTA PEKANBARU - Witasari, Yosi; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Pekanbaru City Community-Based Community Empowerment Program (PMB-RW) is a poverty alleviation program carried out by the Pekanbaru City Government through a process approach to community empowerment with funding from Pekanbaru City APBD, Provincial APBD, APBN, BUMN, BUMD and Corporate Social Responsibility (CSR ) private companies and other non-binding assistance. The PMB-RW activity is a substitute program for the National Community Empowerment Program for Mandiri Rural (PNPM-MP) aimed at creating and increasing community participation in development, both individually and in groups to participate in solving various problems related to efforts to improve the quality of life, independence, and public welfare. The purpose of this study was to determine the community participation in PMB-RW in Tebing Tinggi Okura Village, Pekanbaru City Rumbai Pesisir District and what factors influence community participation. This study uses a type of descriptive research using a qualitative approach.The results of the study are based on the results of interviews and field observations. It is known that community participation in the implementation of the PMB-RW program in Tebing Tinggi Okura can be in the form of money or objects, ideas and thoughts and in the form of labor (mutual cooperation). Based on the results of the study, it is known that community participation in the implementation of the PMB-RW program in Tebing Tinggi Okura Village is still low, this is due to the low level of socioeconomic status of the people living in Tebing Tinggi Okura Village, low average education community, and because of people's busy life in earning a living to meet their daily needs. The factors that become a barrier to community participation in the implementation of the PMB-RW program in Tebing Tinggi Okura Village include internal factors which include (awareness / willingness, education, income / income). And external factors include (Leadership of the Village of Tebing Tinggi Okura and available facilities).Keywords: Community Participation, Community-Based Community Empowerment Program and Tebing Tinggi Okura Village